STUDY OF THE USE OF BIOFILTER REACTOR FOR GREYWATER PROCESSING IN THE AREA OF FLOATING SETTLEMENT KELURAHAN MARGASARI KOTA BALIKPAPAN TOWARD THE CONCEPT OF ZERO WASTE - Jen Supriyanto; Sarto -; Muhammad Sulaiman (ASEAN Journal of Systems Engineering, 2015)
The floating settlement in Margasari is one of the settlements in Kota Balikpapan which is known as a Beach City. PDAM (State Water Company) as the main resource of clean water fulfillment in Balikpapans, needs to needs to be used efficiently. One of the ways is by processing the Greywater which can be reused for toilet flushing in order to support the concept of Zero Waste.The purpose of this research is to obtain the composition and the potential data of Greywater which is appeared from the data and reusable for the citizens, to find out the effectiveness of the use of Biofilter Reactor as an alternative processing unit of Greywater towards the parameters of pH, BOD, COD, TSS, and NH3-N, and also to identify the citizens’ role potential in processing the Greywater towards the concept of Zero Waste in terms of processing domestic liquid waste.The Greywater level in Margasari Floating Settlement of Balikpapan with the parameters of BOD of 520,1–840,1 mg/l, COD of 1.562,5–2.450,0 mg/l, TSS of 297,0–1.047,0 mg/l, and NH3-N of 0,0002-16,257 mg/l is still very high. Margasari Floating Settlement of Balikpapan consists of 6.546 people and 1.198 buldings with an average of Greywater potential of each house of 393,42 l/day or 14.139.360 l/month for the whole area, while the average need for toilet flushing in each house is about 264,03 l/day atau sebesar 9.489.081,60 l/month for the whole area. The Biofilter Reactor can be used to process the Greywater for the whole area. The Biofilter Reactor which has an effective volume of 247 liter, has a diameter of the gravel media of 2,5–4 cm with an optimum effectiveness towards the BOD parameter of 86,54%, COD of 82,27%, TSS of 84,60%, and  NH3-N of 19,99%. It can be used to process the greywater from a house consisted of 5 people with a Greywater debt of 0,36 m3/day, average BOD debt of 686,77 mg/l and average TSS of on Margasari Floating Settlement.